Opportunities and risks of the blue economy for innovative companies in the sustainable aquaculture sector - Miassi, Yann Emmanuel; Dossa, Kossivi Fabrice (Journal of Marine Studies, 2024)
The oceans play a crucial role in the global ecosystem and offer solutions to meet the growing demand for food, water, and energy. However, a new economic concept is needed to regulate and sustainably exploit the maritime resources offered by the marine ecosystem to ensure sustainable development. It is in this initiative that the concept of the blue economy has emerged, in response to the inadequacy of measures taken by States to meet their obligations and achieve their objectives in terms of marine biodiversity conservation. This is how the blue economy concept was born, in response to the inadequacy of state measures to conserve marine biodiversity. This concept proposes an innovative solution integrating aquatic and human resources into sustainable economic activities. The aim of this study is to understand the opportunities and threats that the blue economy represents for innovative companies. This short literature review, based on a SWOT (Strengths, Weaknesses, Opportunities, and Threats) diagnosis of innovative companies, identified a number of obstacles to the development of the blue economy, such as climate change, lack of financing and the lack of instruments for measuring the performance of the blue economy. Action strategies could be implemented to mitigate risks, threats and hazards, and consider an economic approach that reconciles marine and terrestrial ecosystems.